Common wetland plants of Colorado's Western Slope: a pocket guide - Culver, Denise R., author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2018)
The Pocket Guide highlights common wetland plants, both native and non-native located within the Western Slope. It builds upon CNHP's ongoing effort to provide wetlandprofessionals and the general public with essential tools to identify and assess Colorado's wetland resource.
Prepared for: U.S. Environmental Protection Agency, Region 8.
May 2018.
Keywords: Colorado; wetland plants; identification